THE CORRELATION BETWEEN READING SPEED AND READING COMPREHENSION AT THE ELEVENTH - GRADE STUDENTS OF SMK PGRI 3 BADUNG IN ACADEMIC YEAR 2020/2021 - Ester Mei Widiastutik; Putu Ayu Paramita Dharmayanti; Ni Made Wersi Murtini (Academic Journal on English Studies (AJOES), 2022)
This correlational study aims to find out the correlation between reading speed and students’ reading comprehension at the eleventh-grade students of SMK PGRI 3 Badung in academic year 2020/2021. There are two research instruments, they are reading speed test and reading comprehension test. The samples were 10% from the population in eleventh grade students which consist of 38 students. The obtained data was analyzed through pre-requisite and hypothesis analysis. The result of hypothesis testing of this research were r- value is higher than r- table = 0.806 > 0.413. Then, the result showed if the correlation between reading speed and students’ reading comprehension was significant. It means that alternative hypothesis (Ha) is accepted and null hypothesis (Ho) rejected. Considering the explanation before, it could be concluded that there is a significant correlation between reading speed and students’ reading comprehension at the eleventh grade students of SMK PGRI 3 Badung in academic year 2020/2021.